Pengaruh Tingkat Profitabilitas, Ukuran Perusahaan, Risiko Keuangan, Nilai Perusahaan, dan Reputasi Auditor Terhadap Perataan Laba (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2014) - Suryaningsih, Dewi; , Drs. Muhammad Abdul Aris, M.Si (2017)
The objective of this study is to analyze the influence of profitability, firm size, financial risk, firm value, and auditor reputation to income smoothing in manufacturing companies listed in Indonesia Stock Exchange during the period of 2011-2014. Sample was determined by purposive sampling method. From this method, there was collected 128 observations from 32 companies based on logistic regression analysis. The result showed that firm size had positive significantly effect to income smoothing. Auditor reputation had negative significantly effect to income smoothing. Whereas profitability, financial risk, and firm value had no significantly effect to income smoothing. This result were consistent to previous studies from Santoso and Salim (2012), Amanza and Rahardjo (2012), Octavania and Asyik (2014), Noviana and Yuyetta (2011), Dewi and Latrini (2016). Keywords: income smoothing, profitability, firm size, financial risk, firm value, auditor reputation.